Isolation of Human Fibrinogen of High Purity and in High Yield Using Polyethylene Glycol 1000 - Masri, Marwan A; Masri, Saad A; Boyd, Nigel D (Thrombosis and Haemostasis, 1983)
Fibrinogen was isolated from human plasma using a polyethylene glycol 1000 fractionation procedure that eliminates problems of denaturation, degradation and contamination encountered with other procedures (1). The technique is simple, rapid, gives a high yield and gram amounts of fibrinogen can be readily obtained.
Keywords: Human fibrinogen; Isolation; Polyethylene glycol